Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan tentang Kebutuhan Asam Folat pada Ibu Hamil di Wilayah Kerja UPT Puskesmas Pahandut Palangka Raya: The Effect of Health Education on Pregnant Women’s Knowledge Level about Folic Acid Requirement in Pahandut Medical Center Palangka Raya - Merry Delyka; Chrisdianti Yulita; Vina Agustina; Wenie Utonli Sadilah (Jurnal Surya Medika (JSM), 2022)
Background: The length of a normal pregnancy is 40 weeks, counting starts on the first day of the last period. Folic acid during pregnancy is very important because it can help prevent major birth defects. It was found that there was a lack of knowledge among pregnant women about the importance of folic acid during pregnancy. Objective : To know the effect of health education on pregnant women’s knowledge level about folic acid requirement in Pahandut Medical Center Palangka Raya. Method: Pre-Experimental research with one-group pre-test-post test design. The sampling technique is purposive sampling with 25 responses based on inclusion criteria. The data collection instrument uses a questionnaire, and data analysis uses the Wilcoxon rank test. Result: The result of the Wilcoxon statistic test is Sig. (2-tailed) 0.00 that means  = 0.05 and  value (0,000 < 0,05), so Ha is accepted, it shows there is effect of health education on pregnant women’s knowledge level about folic acid requirement. Conclusion: There is effect of health education on pregnant women’s knowledge level about folic acid requirement, so as a medical worker we need to educate about folic acid.